Concepções alternativas e ensino de biologia: como utilizar estratégias diferenciadas na formação inicial de licenciados - Oliveira, Silmara Sartoreto de [UNESP] (2005)
The present work aimed at to diagnose how histology classes of Biological Sciences Course grow in what refers to the students' difficult learning on the scientific concept related to Muscular Tissue. To the evaluation, it was opted for the investigation of the students' alternative conceptions regarding the structure and function of the muscular fiber and for that, an interview was initiated to evaluate the learning difficulties presented by the same ones. The results of this interview guided the organization of a questionnaire to be applied to the students. The answers were appraised in the aspects regarding to the characteristics of the schemes (the students' drawings). It was concluded that the students showed difficulty in the three-dimensional vision of the cell, being difficult to associate the organelles form, location and function, that constitute the muscular fiber. Based on the obtained conclusions it was presented a teaching strategy to go to the encounter of the students' difficulties. Such strategy consisted of several stages. Initially, the professor could investigate the students' alternative conceptions on the content to be administered. In the sequence, the theoretical content would be developed, however the introduction of a problem regarding current situations, would motivate the students to transfer for this practical situation the contents supplied in the theoretical class. It would be important that the professor proposed to their students a differentiated practical activity building a model. With that it is believed that the students may solve the difficulties related to the disposition of the structures, taking advantage of the content learning, favoring teaching situations and learning based on the representation of practical situations for the student.